Role of testosterone in parasitic host behavioral change in Rattus norvegicus : Toxoplasma gondii association - Dhiraj Kumar Singh (2017)
Trophically transmitted parasites are often considered prisoners in the body of their host, relying on incidental predation in order to reach the next stage in their life cycle. In contrast, the 'behavioral manipulation' hypothesis posits that parasites exploit the host behavior to facilitate the transmission. Toxoplasma gondii is a classic example for study the parasitism and the alteration in host behavior. This project is inspired by the loss of fear in rats post Toxoplasma gondii infection. The thesis posits a crucial role for testosterone in mediating parasitic behavioral change in the host. The broad aim is to study the testosterone-amygdalar interactions in behaviorally manipulated Toxoplasma gondii infected male rats. I implement Toxoplasma induced behavioural changes in male rats as a perturbation model to investigate the manipulated defensive mechanism. Elevated testicular testosterone during chronic phase of infection has been well documented. Hence as the first specific aim, I studied necessity and sufficiency of testosterone for behavioral change in Toxoplasma gondii infected male rats. Results show that alterations in fear and concomitant molecular changes can be eliminated when host rats are castrated post establishment of chronic infection. In addition, results demonstrate that exogenous supply of testosterone within medial amygdala of uninfected castrates recapitulates reduction in innate fear akin to behavioral change attributed to Toxoplasma gondii. Overall, these results support a gonadal, rather than brain-dependent, initiation of proximate mechanisms in this association. Most of testosterone is synthesized in Leydig cells of testes and it is mainly regulated by luteinizing hormone secreted by the anterior lobe of pituitary gland. Steroidogenic process in these cells remains under homeostatic control through reciprocal communication with the brain. In view of the reciprocal effects, it is perhaps more appropriate to view medial amygdala where many of parasite-induced changes are observed in the brain and Leydig cells in testes as two nodes of an interacting network. We demonstrate that molecular changes in the medial amygdala cause increase in luteinizing hormone receptor distantly within the testes. In brief, testicular testosterone and medial amygdala epigenetic changes might constitute a positive feed-forward loop capable of self-sustenance once initiated. We investigate the interaction of luteinizing hormone and its testicular receptor during infection by Toxoplasma gondii. This is important because luteinizing hormone receptor is the starting point of signal cascade regulating testosterone production. My experiments in this regard did not highlight any statistically significant findings although this study had sufficient sample numbers. Future studies about alternative mechanisms are thus indicated. In summary, I present a model that is built around pre-existing brain-gonad communication in the host species wherein the parasite uses this pre-existing scaffold to manipulate the host behavior.